Pathology and pathogenesis of vascular cognitive impairment—a critical update - Jellinger, Kurt A. (Frontiers in Aging Neuroscience, 2013)
Vascular cognitive impairment describes a continuum of cognitive diorders ranging from mild cognitive impairment to dementia, in which vascular brain injury involving regions important for memory, cognition and behaviour plays an important role. Classification, prevalence, and pathophysiology are a matter of current research. Clinical diagnostic criteria show moderate sensitivity (ca 50%) and variable specificity (range 64-98%). In Western clinical series, VaD is suggested in 8-10% of cognitively impaired elderly subjects. Its prevalence in autopsy series varies from 0.03 to 58%. In contrast to Alzheimer disease (AD) and mixed dementia showing significant age-related increase, the prevalence of VaD significantly decreases after age 80 years. Cognitive decline is commonly associated with widespread small ischemic vascular lesions involving subcortical brain areas. The lesions affect neuronal networks involved in cognition, memory, and behavior. Cerebrovascular lesions (CVLs) often coexist wth Alzheimer-type lesions and other pathologies. The lesion pattern of "pure" VaD differs from that in mixed dementia (AD + CVLs), which suggests different pathogenesis of both phenotypes. Minor CVLs appear not essential for cognitive impairment in full-blown AD, while both mild AD-type pathology and small vessel disease may interact synergistically in promoting and progressing dementia. However, both AD-related and vascular brain pathologies have been reported. Despite recent suggestions for staging and grading CVLs in specific brain areas, no validated neuropathological criteria are currently available for VaD and mixed dementia. Further clinico-pathological studies and harmonization of neuropathological procedures are needed to validate the diagostic criteria for VaD and mixed dementia in order to clarify the impact of CVLs and other coexistent pathologies on cognitive impairment as a basis for further successful therapeutic options.